Compilation and validation of the puppet show-based social skills training package and its effectiveness on the behavioral problems of the preschoolers - Abbas Sadeghzadeh; Fariborz Dortaj; Hassan Asadzadeh; Ali Delavar; Esma'il Sadipour (Shahid Beheshti University of Medical Sciences, 2023)
Background: The aim of this study was to compile and validate the social skills training (SST) package based on puppet shows and determine its effectiveness on the behavioral problems of preschoolers. Methods: 40 preschool children were selected using available sampling method to evaluate the effectiveness of the compiled package on behavioral problems of preschool children (puppet shows, all components of preschool social skills) using a semi-experimental method with a pretest-posttest design. Then the intervention and the control group were selected. The opinions of the experts were collected by the Delphi method. The research population at this stage was all the specialists in the field of SST of children whom 10 were selected using purposive sampling method. The validity was confirmed using content validity index (CVI). Data of the behavioral problems subscale were collected using the Social Skills Rating System (SSRS), and analyzed using one-way analysis of covariance. Results: The findings showed that the effect of the SST package based on puppet show in the intervention group was statistically significant (F=47.28, P<0.05), so that it was effective in reducing behavioral problems of preschoolers. To validate the package, content validity index (CVI) was used, which was obtained as 0.87. Conclusion: In order to prevent and treat behavioral disorders in children, harmless treatment methods can be replaced physical punishment and verbal aggression. Correct and continuous training of social skills, along with correct and friendly communication with attractive and entertaining methods such as showing puppets to children, can be a solution to improve behavioral problems at this age.